A risk evaluation method to prioritize failure modes based on failure data and a combination of fuzzy sets theory and grey theory. (June 2019) - Wang, Hao; Zhang, Yi-Min; Yang, Zhou
Abstract: Based on the analysis of traditional calculation method of RPN (Risk Priority Number), a risk assessment method for CNC lathes based on failure data and fuzzy set theory combining with grey theory was proposed in this paper. Severity, occurrence and detection were treated as linguistic variables. Meanwhile, failure data was applied and maintenance time was introduced as another variable. Risk prioritization of all the failure modes was obtained through steps such as expert rating, solving α level sets, defuzzification and so on. Grey theory was applied to verify the accuracy of the proposed method. The method was used in a real case of risk analysis of spindle system of a CNC lathe, in which consistency and practicability of the results were illustrated. It can be concluded that the proposed method can take advantage of failure data and control subjectivity in analysis. In addition, importance weights of the four variables were taken into consideration. So that the drawbacks of traditional RPN analysis can be avoided and improvement measures could be made by designers and technologists according to the results so as to improve reliability of CNC lathes.